The use of social media by adults with acquired conditions who use AAC: current gaps and considerations in research. - Paterson, Helen L. (AAC: Augmentative & Alternative Communication, 2017)
The global growth and development of social media has had a positive impact on many individuals who use augmentative and alternative communication (AAC), who use it to communicate and connect with others. Research evidence into the use of social media by adults with acquired conditions who use AAC is limited. These individuals are a heterogeneous population, who can present with a range of linguistic, cognitive and physical needs, some of which progress rapidly, making accessing social media a challenge. These issues warrant research focusing on developing interventions to support the use of social media and the impact of these interventions. For individuals with acquired conditions who have previously used social media and for those who are new to the experience, social media can offer a vital connection to friends, family and health professionals. This paper examines current gaps in knowledge in this area in the field of AAC and proposes potential methodologies for future research. These include combining qualitative and quantitative methodologies (e.g., analysis of online interactions and observational data) that would be useful tools for data collection in an under-researched field.